Banking Policy and the Price Level - Persons, Warren M.; Robertson, D. H. (Quarterly Journal of Economics, 1926)
Journal Article Banking Policy and the Price Level Get access Warren M. Persons Warren M. Persons Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 40, Issue 4, August 1926, Pages 689–698, https://doi.org/10.2307/1884460 Published: 01 August 1926